Hypnosis, Meditation, and Self-Induced Cognitive Trance to Improve Post-treatment Oncological Patients’ Quality of Life: Study Protocol - Grégoire, Charlotte; Marie, Nolwenn; Sombrun, Corine; Faymonville, Marie-Elisabeth; Kotsou, Ilios; van Nitsen, Valérie; de Ribaucourt, Sybille; Jerusalem, Guy; Laureys, Steven; Vanhaudenhuyse, Audrey; Gosseries, Olivia (Frontiers in Psychology, 2022)
Introduction: A symptom cluster is very common among oncological patients: cancer-related fatigue (CRF), emotional distress, sleep difficulties, pain and cognitive difficulties. Clinical applications of interventions based on non-ordinary states of consciousness, mostly hypnosis and meditation, are starting to be investigated in oncology settings. They revealed encouraging results in terms of improvements of these symptoms. However, these studies often focused on breast cancer patients, with methodological limitations (e.g., small sample size, no control group, no follow-up). Another non-ordinary state of consciousness may also have therapeutic applications in oncology: self-induced cognitive trance (SICT). It seems to differ from hypnosis and meditation, as it involves the body more directly. Thus, investigating its clinical applications, along with hypnosis and meditation interventions, could improve available therapeutic options in oncology. This article details the study protocol of a preference-based longitudinal controlled superiority trial aiming to assess the effectiveness of 3 group interventions (hypnosis, meditation and SICT) to improve oncological patients' quality of life, and more specifically CRF, emotional distress, sleep, pain and cognitive difficulties (primary outcomes). Methods and analysis: A power analysis required a total sample of 160 patients. Main inclusion criteria are: cancer diagnosis, active treatments completed for less than a year, no practice of hypnosis, meditation or SICT, and presence of one of these four symptoms: fatigue, sleep difficulties, depression or anxiety. Each participant will choose the intervention in which they want to participate (hypnosis, mindful self-compassion meditation, SICT, or no intervention - control group). To test the effectiveness of the interventions, data will be collected by questionnaires and neurobiological measures, and directly from the medical record at four time points: before inclusion in the study (baseline); immediately after the intervention; and at 3- and 12-month follow-up. The longitudinal data in each group will then be measured. Discussion: In addition to standard cancer therapies, there is a growing interest from patients in complementary approaches, such as hypnosis, meditation and SICT. The results of this study will be useful to increase knowledge about short and long-term effectiveness of 3 group interventions for CRF, emotional distress, sleep, pain and cognitive difficulties in patients with different cancers.